Lithuanian reflexive-based impersonals with accusative objects - Spraunienė, Birutė; Žeimantienė, Vaiva (Vilnius University Open Series, 2021)
This paper surveys Lithuanian impersonal constructions with predicative present passive participles containing non-promoted accusative objects. It is shown that the construction, hitherto considered very rare, is well-attested and productive with one verb class, namely, transitive reflexives. In terms of semantics, transitive reflexives in Lithuanian may be classified as autobenefactives. Autobenefactive reflexives do not exhibit a change in argument structure with respect to their non-reflexive counterparts. In the case of autobenefactives, the morpheme -si- attached to the verb adds the meaning that the subject, which mostly has the semantic role of an agent, benefits from the event expressed by the predicate. On the basis of corpus data, we have analysed how widespread impersonal constructions with accusative objects are within the domain of transitive reflexives and which pattern—the accusative or the nominative—is dominant when both are attested. Lastly, we briefly discuss the temporal-aspectual meaning of reflexive-based impersonals as well as the referential properties of implied agents